Poor efficacy of anti‐programmed cell death‐1/ligand 1 monotherapy for non‐small cell lung cancer patients with active brain metastases. Issue 9 (12th July 2020) - Tozuka, Takehiro; Kitazono, Satoru; Sakamoto, Hiroaki; Yoshida, Hiroshi; Amino, Yoshiaki; Uematsu, Shinya; Yoshizawa, Takahiro; Hasegawa, Tsukasa; Ariyasu, Ryo; Uchibori, Ken; Yanagitani, Noriko; Horai, Takeshi; et al.
Abstract : Background: The efficacy of anti‐programmed cell death‐1/ligand 1 antibody monotherapy (anti‐PD‐1/PD‐L1 monotherapy) in patients with active brain metastases (BMs) is not established. Here, we aimed to evaluate the efficacy of anti‐PD‐1/PD‐L1 monotherapy in non‐small cell lung cancer (NSCLC) patients with active BMs. Methods: This retrospective study included NSCLC patients treated with second‐line or later‐line anti‐PD‐1/PD‐L1 monotherapy between December 2015 and August 2019. Patients were classified into those with or without active BMs, including symptomatic BMs requiring systemic steroids and untreated BMs. The progression‐free survival (PFS) and overall survival (OS) of the patients with and without active BMs were compared. Intracranial and extracranial tumor responses were evaluated in patients with active BMs. Results: We analyzed 197 patients who had received anti‐PD‐1/PD‐L1 monotherapy. Among them, 24 had active BMs. Among those without active BMs, 145 had no BMs and 28 had treated asymptomatic BMs. The PFS and OS of patients with active BMs were significantly shorter than those of patients without active BMs (1.3 vs. 2.7 months; P  < 0.001, and 4.5 vs. 16.3 months; P = 0.001 respectively). For patients with active BMs, the intracranial and extracranial response rates were 13.3% and 26.7%, respectively. On multivariate analysis, active BMs, poor performance status (PS), and EGFR/ALK positivity were significant factors associated with shorter PFS. Active BMs and poor PS were significant factors associated with shorter OS. Conclusions: This study suggested that anti‐PD‐1/PD‐L1 monotherapy was not effective for NSCLC patients with active BMs. Further studies on immunotherapy are needed for patients with active BMs. Key points: Significant findings of the study: The present study showed that anti‐PD‐1/PD‐L1 antibody monotherapy was not effective for non‐small cell lung cancer patients with active brain metastases. Intracranial and extracranial response rates were 13.3% and 26.7%, respectively. What this study adds: Further studies on immunotherapy are needed for patients with active BMs. Abstract : The present study showed that anti‐PD‐1/PD‐L1antibody monotherapy was not effective for non‐small cell lung cancer patients with active brain metastases. Intracranial and extracranial response rates were 13.3% and 26.7% respectively. Further studies on immunotherapy are needed for patients with active BMs.